Team Building and Motivation: A Key Factor in Nursing Management Using VIKOR Method - Manjula Selvam (Contemporaneity of English Language and Literature in the Robotized Millennium, 2026)
This study employed the VIKOR method to evaluate and rank essential nursing leadership qualities in healthcare settings, addressing the increasing complexity of healthcare management amid resource constraints and technological advancement. The research analysed five critical leadership attributes: emotional intelligence, decision-making skills, communication skills, adaptability and resilience, and team building and motivation. These qualities were assessed across four primary dimensions: performance appraisals, self-assessment tools, patient and staff outcomes, and real-time observations and simulations. The findings revealed decision-making skills as the highest-ranked leadership quality, particularly excelling in patient and staff outcomes (90.26). Team building and motivation emerged as the second most crucial attribute, demonstrating strong performance in outcomes (89.46). Emotional intelligence ranked third, showing particular strength in real-time observations (89.43). Communication skills and adaptability, though ranked fourth and fifth, respectively, exhibited notable effectiveness in specific areas, with communication skills achieving high scores in performance assessments (78.09) and adaptability showing exceptional results in patient and staff outcomes (97.12). The VIKOR analysis utilized 𝑆𝑗 (coherence scale), 𝑅𝑗 (regret scale), and 𝑄𝑗 (compromise rank measure) to provide a comprehensive evaluation. Notably, adaptability and resilience achieved the optimal 𝑄𝑗 score (0), indicating superior balance across evaluation criteria despite their overall lower ranking. This discrepancy highlights the multifaceted nature of leadership assessment in healthcare settings. The study’s findings have significant implications for nursing leadership development programs and recruitment strategies, suggesting a need for prioritizing decision-making skills while maintaining a holistic approach that integrates all five leadership qualities. This balanced approach aligns with contemporary healthcare demands, where leaders must effectively navigate technological changes, resource limitations, and increasing patient complexity while maintaining high standards of care